FAKTOR-FAKTOR YANG MEMPENGARUHI KELANGKAAN GULA AREN DI KECAMATAN RAMBAH KABUPATEN ROKAN HULU - wulan, wulan_safrianii; Fitriana, Laily; Febrinova, Rina (Universitas Pasir Pengaraian, 2025)
The availability of scarce palm sugar is influenced by several factors, based on these factors, it will be seen how much it affects the scarcity. The purpose of this study is to look at and find out the factors that affect the scarcity of palm sugar. This data analysis technique uses multiple linear regression analysis techniques. The results showed that the factors that affect the scarcity of palm sugar in Rambah District, Rokan Hulu Regency are high demand at a certain time (X2), delay in distribution (X3), limited knowledge (X4), and unethical practices (X5), while limited natural resources (X1) have no effect, but simultaneously all independent variables have a significant effect on the dependent variables. The determination coefficient shows that the influence is 63%, so there are 37% of other factors that are not explained in this study.